M2-LIKE MACROPHAGES ARE POTENTIAL CANDIDATES FOR BRAIN STROKE OUTCOMES' TREATMENT - S. A. Morozov; G. V. Tomash; E. Ya. Shevela; L. V. Sakhno; A. V. Smyk; N. M. Starostina; A. A. Ostanin; E. R. Chernykh (Acta Biomedica Scientifica, 2012)
The safety and effectiveness of in vitro generated M2-like macrophages for treatment of patients with ischemic and hemorrhagic brain stroke in reparative and residual periods has been evaluated. A single endolumbar administration of autologous M2-like macrophages in the mean dose of 17,9 х 106 cells was conducted in 13 patients with ischemic (n = 10) and hemorrhagic (n = 3) brain stroke. At 6 months after cells administration all the patients had clinical Improvement. NIHS score decreased from 8,6 ± 1,06 to 4,4 ± 0.55 (p = 0,0008), several patients showed the decrease of sensitiveness impairments, improvement of cognitive functions and enhanced quality of life. Thus, we demonstrated an ability of generation M2-like macrophages from patients with brain stroke. Endolumbar administration of these cells was safe andi didn't cause severe adverse effects and complications andi — in preliminary data — improvedi motional and cognitive functions.